1998
DOI: 10.1142/s0218127498001170
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation and Chaos in Noninteger Order Cellular Neural Networks

Abstract: In this paper a new class of Cellular Neural Networks (CNNs) is introduced. The peculiarity of the new CNN model consists in replacing the traditional first order cell with a noninteger order one. The introduction of fractional order cells, with a suitable choice of the coupling parameters, leads to the onset of chaos in a two-cell system of a total order of less than three. A theoretical approach, based on the interaction between equilibrium points and limit cycles, is used to discover chaotic motions in frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(56 citation statements)
references
References 9 publications
0
56
0
Order By: Relevance
“…Remark 1. Assumption 1 can be seen in many literatures [3,13,[15][16][17][18][19][22][23][24]. Besides, different from most of above works, in this paper, we assume that the Lipschitz constant L i is unknown.…”
Section: Assumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 1. Assumption 1 can be seen in many literatures [3,13,[15][16][17][18][19][22][23][24]. Besides, different from most of above works, in this paper, we assume that the Lipschitz constant L i is unknown.…”
Section: Assumptionmentioning
confidence: 99%
“…Consequently, many researchers utilize fractional-order calculus in neural networks to construct fractional-order neural networks, which can be more appropriate to describe the dynamical behavior of the neurons in neural networks, such as "memory". In [11], Arena et al first give a cellular neural network with fractional-order cells. In [12], Petráč introduces a fractional-order 3-cell network which exhibits limit cycles and stable orbits for different parameter values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, bifurcations and chaos phenomenon in FONNs are studied in [12][13][14]. In [15], energy-like functions are utilized to study the stability of FONNs.…”
Section: Introductionmentioning
confidence: 99%
“…Hartley et al introduced the fractional-order Chua's system and showed that with the order less than 3, the chaotic behavior is still possible [20]. In [21], the fractional-order cellular neural network was considered, and Ibrahima N'Doye and Taous-Meriem Laleg-Kirati are with Computer, Electrical and Mathematical Sciences and Engineering Division (CEMSE), King Abdullah University of Science and Technology (KAUST). Thuwal 23955-6900, KSA.…”
Section: Introductionmentioning
confidence: 99%